2008
DOI: 10.1210/jc.2007-1154
|View full text |Cite
|
Sign up to set email alerts
|

The Risk of Second Primary Malignancies up to Three Decades after the Treatment of Differentiated Thyroid Cancer

Abstract: The overall risk of second primary malignancies is increased for thyroid cancer survivors and varies by radioisotope therapy, latency, and age at diagnosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

14
312
5
6

Year Published

2008
2008
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 342 publications
(337 citation statements)
references
References 38 publications
14
312
5
6
Order By: Relevance
“…Considering the excess in solid cancers, and the type of tumours concerned, the data are highly divergent in the literature. Some authors [13] have reported a link between 131 I therapy and some solid cancers, which has not been confirmed by other studies [14].…”
mentioning
confidence: 80%
“…Considering the excess in solid cancers, and the type of tumours concerned, the data are highly divergent in the literature. Some authors [13] have reported a link between 131 I therapy and some solid cancers, which has not been confirmed by other studies [14].…”
mentioning
confidence: 80%
“…In 2003, Rubino et al [37] reported that cumulative doses of RAI (Ͼ600 MCi, 22 GBq) are associated with a higher risk for leukemia. A greater risk for other secondary malignancies has also been reported [38,39]. Thus, the use of RAI should be individualized to balance the risks against the therapeutic benefit.…”
Section: Raimentioning
confidence: 99%
“…According to the American Thyroid Association (ATA) recommendations, after total thyroidectomy, 131-I administration is indicated in patients with moderate to high risk of recurrence based on age, tumour size, lymph node status, extrathyroidal extension, and the histological type of the thyroid tumour (Cooper et al 2009;Schlumberger and Sherman 2012). However, the significant radiation doses delivered to extrathyroidal tissues are associated with acute and long-term risks and side effects, including second primary malignancies (Rubino et al 2003;Brown et al 2008;Sawka et al 2009). …”
mentioning
confidence: 99%